Fungal Gastrointestinal Translocation is Associated with Immune Activation and Systemic Inflammation in Treated HIV. (4th October 2017) - Weiner, Lukasz; Retuerto, Mauricio; Hager, Christopher; El Kamari, Vanessa; Sattar, Abdus; Ghannoum, Mahmoud; Dirajlal-Fargo, Sahera; McComsey, Grace A
Abstract: Background: The mechanisms causing HIV-associated immune activation remain incompletely understood, but alteration of intestinal integrity and resultant translocation of microbial products appear to play a key role. The impact of intestinal fungal translocation and its association with immune activation and cardiovascular disease (CVD) remains a largely unexplored domain. Methods: We performed a cross-sectional analysis of HIV-infected participants on with HIV-1 RNA < 1, 000 copies/mL and HIV-uninfected healthy controls. We measured several serum fungal markers [1, 3-β-d -glucan (BDG) and anti- Saccharomyces cerevisiae antibodies (ASCA) IgG and IgA], and markers of systemic inflammation and monocyte activation. T-test and Mann–Whitney tests were used to compare markers by HIV status and correlation and regression analyses were used to assess associations of fungal translocation markers with markers of inflammation and pulse wave velocity (PWV), a measure of arterial stiffness. Results: Overall, 178 participants were included in the study (130 HIV+ and 48 HIV-); 73% were male; 65% African American; median age was 50 years and CD4 was 710 cell/cm 3 . As shown in Figure 1, levels of BDG were lower in HIV+ when compared with controls ( P = 0.04). There was no significant difference in levels of ASCA IgG and IgA between groups ( P >0.65). There was a significant correlation between BDG and several markers of inflammation and immune activation, but not with ASCA IgG and IgA (Table 1). Both BDG and ASCA IgA significantly correlated with PWV. However, after adjusting for TNFRii and Ddimer, fungal markers were no longer associated with PWV (β = −0.00006, P = 0.94 and β = 0.009, P = 0.51). Conclusion: HIV+ participants on ART do not have higher levels of BDG or ASCA when compared with uninfected controls. In this exploratory study, our results suggest a potential role of fungal translocation in the heightened inflammation and immune activation seen in treated HIV. Disclosures: G. A McComsey, Gilead: Consultant, Consulting fee and Research support. BMS: Consultant, Consulting fee and Research support. GSK/ViiV: Consultant, Consulting fee and Research support. ICON: Consultant, Consulting fee. Merck: Investigator, Research support